Cognitive Development by Zone of Proximal Development (ZPD): Gettier problem & Corpus Linguistics in Epistemology - Gehlot, Lalit (Journal of Education Culture and Society, 2021)
Aim/Thesis: The aim of this research is to promote the use of the three concepts– the Zone of Proximal Development (ZPD), the Gettier Problem, and Corpus Linguistics (Contextual Learning)–to increase the academic performance of early undergraduate engineering students. Concept/Methods: 30 Engineering students completed one untimed Mensa IQ Test of 10 questions and one Simon-Binet IQ Test of 50 random IQ questions with a 12 minute time limit. These 30 students were chosen from two different college sections: 15 students from each section. Before the second Simon-Binet Test, one group, G(a), was given ZPD scaffolding in three major topics — Working Memory, Fluid Reasoning and Spatial Reasoning —as they had answered questions based on these concepts incorrectly in their first Mensa IQ test. The second group, G(b), was not given the ZPD scaffolding. A statistical t-test that was later performed indicated that G(a), with scaffolding, outperformed G(b), without the scaffolding, in the second IQ test. Results and conclusion: Using the t-test, it is seen that the hypothesis of this research that ZPD, Gettier Problem and Corpus Linguistics can enhance the performance of the students in a short time period is correct. After the first Mensa IQ test, the level of both the groups G(a) and G(b) of engineering students was almost the same, indicated by a very similar mean results. However, after supporting G(a) utilizing ZPD, Gettier Problem and Corpus Linguistics for their three problem areas - Working Memory, Fluid Reasoning and Spatial Reasoning - identified after their first IQ test where the students needed scaffolding, the performance of this group improved more in comparison to G(b), as indicated by the results of the second online Simon-Binet Test. Research restrictions: It was not possible to provide all the random questions of the online Simon-Binet test given to all 30 students because the total number of questions would be 30*50=1500. Only the first ten questions of the Mensa IQ test are included in this research paper. Further, the third and fourth year engineering students are not included in this research as it is assumed that they have had already developed expertise and the effect of the investigated tools would not be clearly visible. Practical application: ZPD scaffolding was applied to the students when the students’ major problem areas were identified as requiring contextual learning and support. The Gettier Problem– an epistemological concept– was also used to keep their mind open at all the times during the learning process and Linguistics Corpus gave the contextual support as ZPD proposes the social-contextual mode of learning. Originality/Cognitive value: The paper presents empirical research on engineering students demonstrating the practical utility of ZPD, Gettier Problem and Corpus Linguistics in the process of learning, potentially irrespective of any discipline.